Promoting healthier diets in India through “Front of Package Food Labeling” - Bera, Om Prakash; Saleem, Sheikh Mohd; Bhattacharya, Sudip (Indian Journal of Community Health, 2021)
The rising NCDs are attributed to an epidemiological health transition resulting from rapid urbanization, sedentary lifestyle, and transforming nutritional preferences. The behavioral risk factors like the adoption of a sedentary lifestyle and changing dietary pattern have resulted in the consumption of an unhealthy diet, building up and less burning of calories. It has been observed that nutrition labeling has played a crucial role in shaping consumer level food behavior. Many labeling systems have been proposed and designed as per country specific needs. Consumers face many challenges while accessing the food packets, small fonts, labeling on the back side, not understanding its language, and unable to evaluate the nutritional information which is described on the packets. Our aim should be to improve the information available within the food package, increase food information accessible to the people, and more importantly, the use of this information must be brought into service by the consumers as to make healthy food choices. Chile's approach to warning labels is currently considered the gold standard in the FOPL system, which have significantly reduced the consumption of unhealthy foods by people. There is a need to introduce the replica of the same Chile’s FOPL system in India. It's time to make the right move and make India a global leader in FOPL food systems by the introduction of strong and stringent FOPL laws that may help consumers with informed food choices and FSSAI may play a leadership role in this.